A QUALITATIVE NEEDS ANALYSIS OF SQ3R-BASED DIGITAL LEARNING WORKSHEETS IN PRIMARY SCHOOL READING ACTIVITIES - Agustin Vera Dewi; Seni Apriliya; Lutfi Nur (Jurnal Cakrawala Pendas, 2025)
Learner Worksheets (LKPD) have an important role in learning to read in elementary schools, but the application of LKPD in the field still faces obstacles, such as unattractive appearance, limited content, and practicality. The printed LKPD used is not fully interactive, thus affecting students' interest and reading comprehension. The lack of variety in the presentation of material also reduces the effectiveness of learning. Therefore, innovation in the form of digital LKPD based on the SQ3R strategy is needed to improve reading learning. This study aims to analyze the need for the development of SQ3R-based digital LKPD. Using descriptive qualitative research method, data were collected through document analysis of LKPD and interviews with four grade VI teachers in Gugus 1 Karangnunggal District. The results showed that the current LKPDs were less interesting and did not support comprehensive text comprehension. The SQ3R strategy (Survey, Question, Read, Recite, Review) has the potential to be a solution because it can increase students' involvement in understanding the text in a more structured manner. In addition, digital LKPD allows the integration of multimedia elements that enrich the learning experience. As a reference, the PISA study shows the importance of a systematic reading approach to improve student comprehension. Thus, the development of SQ3R-based digital LKPD is an urgent need to improve the quality of reading learning in elementary schools.